A new and previously misidentified species of Trisetella (Pleurothallidinae: Orchidaceae) from southeast Ecuador - Baquero, Luis E.; Mogrovejo, Adriana L. (Lankesteriana: International Journal on Orchidology, 2021)
Trisetella pachycaudata, a new species in the subtribe Pleurothallidinae, was discovered in the Zamora Chinchipe province of southeast Ecuador, and it is described here. Trisetella pachycaudata is compared with the most similar species (and others with which it has been confused in cultivation), T. triglochin, T. strumosa, and T. vittata. It differs from them in the flowers with a much thicker apex of the sepaline tails (the thickest in the genus), and the petals expanded at the labellar margin, with the cuspidate apices erose on the upper margin and entire at the lower margin. Key words / Palabras clave: Trisetella strumosa, Trisetella triglochin, Trisetella vittata, Zamora Chinchipe